Bone-derived soluble factors and laminin-511 cooperate to promote migration, invasion and survival of bone-metastatic breast tumor cells. (April 2014) - Denoyer, Delphine; Kusuma, Nicole; Burrows, Allan; Ling, Xiawei; Jupp, Lara; Anderson, Robin L.; Pouliot, Normand
Abstract Tumor intrinsic and extrinsic factors are thought to contribute to bone metastasis but little is known about how they cooperate to promote breast cancer spread to bone. We used the bone-metastatic 4T1BM2 mammary carcinoma model to investigate the cooperative interactions between tumor LM-511 and bone-derived soluble factors in vitro. We show that bone conditioned medium cooperates with LM-511 to enhance 4T1BM2 cell migration and invasion and is sufficient alone to promote survival in the absence of serum. These responses were associated with increased secretion of MMP-9 and activation of ERK and AKT signaling pathways and were partially blocked by pharmacological inhibitors of MMP-9, AKT-1/2 or MEK. Importantly, pre-treatment of 4T1BM2 cells with an AKT-1/2 inhibitor significantly reduced experimental metastasis to bone in vivo. Promotion of survival and invasive responses by bone-derived soluble factors and tumor-derived LM-511 are likely to contribute to the metastatic spread of breast tumors to bone.